PEREMPUAN ACEH: ANTARA BUDAYA DAN SYARI'AT - Abd. Wahid (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2010)
Acehnese women demand that the implementation of Islamic law must be suited to cultural context, Acehnese culture. The rapid change of today's lifestyle forces acehnese women to hardly preserve these two patterns; islamic law and culture. Large number of acehnese women have showed their strong commitment to live and act in form of "Islamic Acehnese women". It is based on their beliefs that living and acting among acehnese community must be rooted from Aceh culture and islamic value. However, this condition has been misinterpreted and assumed as a part of islamic teaching